Analysis Of The Role Of Leadership In Improving The Performance Of Cigugur Central City Cimahi City Office Employees - Tanti Tresnawati; Lies Anggi Puspita Dewi (Sean Institute, 2024)
Leadership is the process of directing and giving influence to group members who are interconnected with the same task. A good leader who can apply leadership skills that are appropriate to the work situation they will face can certainly motivate their employees to work as optimally as possible, this can make employee performance better. This research is located at the Cigugur Tengah Subdistrict Office, Cimahi City. This research was conducted to determine the role of interpersonal roles, decision making, informational roles in improving employee performance. This research uses a qualitative descriptive method with data collection techniques through interviews, observation and documentation. The resource persons for this research were the Secretary of Cigugur Tengah Subdistrict and the employees of Cigugur Tengah Subdistrict. The data analysis carried out is data reduction, data presentation and finally drawing conclusions. The leadership role is an important role that influences improving employee performance at the Cigugur Tengah Subdistrict Office. There are several other factors that will improve employee performance, such as honesty, time discipline, accuracy in completing tasks, ability to work together and willingness to learn.